DAMPAK PEMBERIAN REWARD DAN ICE BREAKING TERHADAP MINAT DAN HASIL BELAJAR PADA MATA PELAJARAN IPA SISWA KELAS IV SD NEGERI 24 LAHAT - Bella Martha Fadila; Suratmi (PGSD UNIKA SANTU PAULUS RUTENG, 2024)
This study aims to description the impact of giving rewards on learning interest in natural science subjects of grade IV students of SD Negeri 24 Lahat, impact of giving ice breaking on learning interest in natural science subjects of grade IV students of SD Negeri 24 Lahat, impact of giving rewards on learning outcomes in natural science subjects of grade IV students of SD Negeri 24 Lahat, impact of giving ice breaking on learning outcomes in natural science subjects of grade IV students of SD Negeri 24 Lahat. The type of research used is experimental. Quasi experimental as the research method used. The research design used a one shot case study. The subjects of this study numbered 30 students. Data collection techniques using questionnaires and post tests. Data analysis techniques use the average of values. Based on the results of the study, there is an impact of giving rewards and ice breaking on learning interest in science subjects of grade IV students of SD Negeri 24 Lahat. Giving star stickers as a form of reward has succeeded in mobilizing students' interest, so they become more involved in answering questions in order to achieve the sticker. The existence of ice breaking makes the atmosphere that previously felt monotonous become more cheerful and enthusiastic, the brain will experience changes to be fresher to understand the explanation of the material from the teacher. There is an impact of giving rewards and ice breaking on learning outcomes in science subjects of grade IV students of SD Negeri 24 Lahat. Giving rewards encourages students to learn, do many questions and will make them able to answer the learning outcomes test questions well. The use of ice breaking techniques can basically create a fun learning atmosphere so that students become interested and motivated to learn the material being taught.